The Theoretical Evaluation of Clioquinol Electrochemical Determination over Squaraine Dye/CuS Composite - Tkach, V. V.; Kushnir, M. V.; de Oliveira, S. C.; Ivanushko, Y. G.; Yagodynets', P. I.; da Silva, A. O.; Derevianko, N. P.; Zavhorodnii, M. P.; Serhata, N. S.; Serhatyi, M. O.; Bandurina, K. V.; Baryshok, T. V.; et al. (My University, 2025)
In this work, the electrochemical determination of clioquinol on the electrode, modified by the squaraine dye complex with copper sulfide nanoparticles, is described. The electroanalytical process begins with the analyte hydrolysis, followed by its hybrid oxidation by the pyridinic nitrogen atom and the hydroxyquinole moiety. The indirect electropolymerization scenario, in its turn, isn´t discarded either. The analysis of the correspondent model indicates the efficiency of the aquaraine dye/nano-CuS composite as an efficient electrode modifier for clioquinol electrochemical determination. The electroanalytical process is easy to conduct, and the analytical signal is easy to interpret. Contrarily to the acidic medium, the possibility of oscillatory and monotonic instability is less expressed.
Keywords: clioquinol; electrochemical sensor; squaraine dyes; copper (II) sulfide; stable steady-state